HUBUNGAN STATUS SOSIAL EKONOMI DENGAN PERSEPSI ORANG TUA TERHADAP PENDIDIKAN SEKS PADA ANAK USIA 4-6 TAHUN DI KELURAHAN LABUH BARU TIMUR KECAMATAN PAYUNG SEKAKI KOTA PEKANBARU - Rosauli Rosauli; Zulkifli Zulkifli; Febrialismanto Febrialismanto (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: Based on observations made in Labuh Baru Timur Village, Payung Sekaki Subdistrict, Pekanbaru City, there are phenomena that occur such as: 1) parents who consider sex education in children not important, 2) lack of knowledge of parents in providing an understanding of sex education in children, 3) parents do not care about what their children have done and there are parents who think that their childrendo not know about sex.The purpose of this study was to determine the relationship of socioeconomic status with perceptions of parents on pedidical sex in children aged 4-6 years in the East Labuh Baru Village Payung Sekaki District, Pekanbaru City. to determine the sample of this study, the researcher used a saturated sample technique, which is to determine the sample by taking it as a whole. The number of samples in this study were 39 respondents. The data collection techniques used are through questionnaires. in this study the proposed hypothesis is the relationship of socioeconomic status with the perception of parents on sex education in children aged 4-6 years. From the test results, the value of X2 count> X2 table = 12,198> 9,488 or P value <alpha = 0,016 <0,05. It can be interpreted that there is a relationship between work and parents' perceptions of sex education in children aged 4-6 years in LabuhBaru Timur Village, Payung District, Pekanbaru City. From the test results, the value of X2count> X2table = 15,501> 12,592 or P value <alpha = 0,017 <0,05. It can be interpreted that there is a relationship between the level of education and parental preferences for sex education in children aged 4-6 years in the East Labuh Baru Village, Payung Sekaki District, Pekanbaru City. From the test results, the value of X2count <X2table = 8.320 <12.592 or P value> alpha = 0.216> 0.05. It can beinterpreted that there is no relationship between income and parental preferences for sex education in children aged 4-6 years in Labuh Baru Timur Village, Payung Sekaki District, Pekanbaru City.Key Words: Socio-Economic, Sex Education, Perceptions